Vinpocetine Protects Against Cerebral Ischemia-Reperfusion Injury by Targeting Astrocytic Connexin43 via the PI3K/AKT Signaling Pathway - Zhao, Mingming; Hou, Shuai; Feng, Liangshu; Shen, Pingping; Nan, Di; Zhang, Yunhai; Wang, Famin; Ma, Di; Feng, Jiachun (Frontiers in Neuroscience, 2020)
Vinpocetine (Vinp) is known for its neuroprotective properties. However, the protective mechanism of Vinp against cerebral ischemia/reperfusion (I/R) injury should be further explored. This study was designed to investigate the neuroprotective effects of Vinp against oxygen-glucose deprivation/reoxygenation (OGD/R) injury in vitro and cerebral I/R injury in vivo and explore whether this mechanism would involve enhancement of astrocytic connexin 43 (Cx43) expression via the phosphatidylinositol 3-kinase/protein kinase B (PI3K/AKT) pathway. In vitro, we detected astrocytic viability and extracellular nitric oxide by an assay kit, intracellular reactive oxygen species by a DCFH-DA probe, inflammation and apoptosis-related protein expression by immunofluorescence staining, and the astrocytic apoptosis rate by flow cytometry. In vivo, we measured the cerebral infarction volume, superoxide dismutase activity, malondialdehyde content, and the expression of inflammation and apoptosis-related proteins. The results indicated that Vinp ameliorated the detrimental outcome of I/R injury. Vinp attenuated astrocytic injury induced by OGD/R and reduced cerebral infarction volume and cerebral edema in rats with cerebral I/R injury. Moreover, Vinp reduced oxidative stress, inflammation, and apoptosis induced by cerebral I/R injury in brain tissues. Meanwhile, Vinp increased p-Cx43 and p-AKT expression, and the p-Cx43/Cx43 and p-AKT/AKT ratio, which was decreased by cerebral I/R injury. Coadministration of PI3K inhibitors LY294002 and BKM120 blunted the effects of Vinp. This study suggests that Vinp protects against cerebral I/R injury via Cx43 phosphorylation by activating the PI3K/AKT pathway.